Penerapan Skema Pemberdayaan Ekonomi Masyarakat Berbasis Dana CSR Syariah: Studi Kasus pada PT Spektra Megah Semesta Jakarta - Alfiyandra, Muhammad Fauzaan; Tamimi, Yusrina Alyani; Lisnawati, Rika; Alyssa, Heidy Puspa (Warmadewa Economic Development Journal (WEDJ))
Corporate Social Responsibility is the company's commitment to participate in sustainable economic development in order to improve the quality of society and the environment that is beneficial, both for the company itself, the local community, and society in general The implementation of CSR that is sustainable by the company is one of the efforts to prevent crisis by strengthening the company's reputation and image. The purpose of CSR activities is to establish positive social relations with the community so that foster favorable public attitudes (favorable) company. Steps that are aligned with the public interest will bring sympathy and increase public trust in the company. This research aims to determine the application of Corporate Social Responsibility (CSR), as well as to determine the benefits of the application of Corporate Social Responsibility (CSR) at PT Spektra Megah Semesta Jakarta. The method used in this research is descriptive method and qualitative analysis with a research focus on the application, and the benefits of CSR through programs that have been run by PT. Spektra Megah Semesta Jakarta Period 2020-2024.